Razão cintura-estatura como marcador antropométrico de risco à saúde: estudo de base populacional em adultos e idosos brasileiros. - Corrêa, Márcia Mara (2016)
Overweight has been considered one of the major aggravating factors in health and significantly contributes to the increase in morbidity-mortality. The issue must be monitored through nutritional surveillance actions aiming to adequate public policies on the prevention, promotion, and recovery of health. Thus, several nutritional assessment methods have been recommended, especially anthropometry given its convenience, low cost, and precise diagnosis, with widespread use of body mass index, waist circumference, and waist-to-hip ratio. More recently, the ratio between waist circumference and height has been proposed as an anthropometric measure to assess core adiposity since it is strongly associated with cardiometabolic risk factors and related to mortality regardless of body weight. This anthropometric marker circumvents the limitations of waist circumference by including height in the index, which prevents potential confounding of height in cardiometabolic risk. This measure has also been suggested as a health risk marker instead of the combination matrix between body mass index and waist circumference for its greater ability of early identification of persons at risk. With that in mind, the present thesis aimed to carry out a systematic review on the validity of the waist-to-height ratio as an anthropometric measure to diagnose adiposity in the elderly population and its association with non-communicable diseases and disorders. The review also sought to identify the cut-off point of this marker with greater sensitivity, specificity, and accuracy for this population by using the body mass index as an anthropometric reference and, finally, to assess whether the waist-toheight ratio is as able to identify health risks as the association matrix between the body mass index and waist circumference in both adults and elderly persons. Data on a household-based epidemiologic survey with a representative sample of the Brazilian population between 2008 and 2009 were used. The sample comprised 8,235 adults and 5,494 elderly persons with the anthropometric measures required for the analyses proposed who lived in the urban areas of 100 small, medium-sized, and large municipalities of the 23 states of Brazil. The first original paper used the ROC (Receiver Operating Characteristic) curve to determine the ideal cut-off point of the waist-to-height ratio as a marker for overweight, using the body mass index as an anthropometric reference. The second original paper featured analyses of the prevalence ratio so as to verify the association between systemic arterial hypertension and the health risk categories assessed by the waist-to-height ratio and by the association between the body mass index and waist circumference. The results presented show that the waist-to-height ratio is a simple measure that has good predicting power as an anthropometric marker of overweight. In addition, the waist-to-height ratio identified more persons at early health risk compared to the combination matrix between the body mass index and waist circumference and showed comparable ability to identify health risk irrespective of sex or age group regarding prevalence ratios for arterial hypertension. That shows the waist-to-height ratio is a useful and effective measure both for professionals and for healthcare managers. Thus, we recommend and incentive the use of the waist-to-height ratio as a measure to replace the body mass index and its association with waist circumference both in epidemiological research and in individual and collective clinical practice as an anthropometric marker of health risk.